PENINGKATAN KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI PENDAMPINGAN BERBASIS BIMBINGAN INDIVIDU DI SMAN 2 PASAMAN - Gustirizal Gustirizal (STKIP Pesisir Selatan, 2020)
Based on observations and supervision conducted by the author shows that the teachers at SMAN 2 Pasaman do not have the ability and good skills in carrying out their duties, especially in terms of using learning media. The purpose of this study was to describe and obtain information about efforts to improve the ability of teachers to use instructional media by providing mentoring based on individual guidance at Pasaman High School 2. This research is a School action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 7 class teachers at SMAN 2 Pasaman. Research data were collected using observation sheets. Data were analyzed using averages. The results showed that mentoring activities based on individual guidance can improve the ability of teachers in designing, determining and using learning media. This is evidenced based on preliminary data on the ability of teachers before the implementation of mentoring activities based on individual guidance is still in the unfavorable category. Then after mentoring activities based on individual guidance, the ability of teachers increases as seen from the improvement in the quality of instructional media made by teachers and the increase in the ability of teachers to use the media in the classroom to 77.71 (good) in the first cycle and after that increases in the second cycle to 86 (very good).